Strength of materials a unified theory - Patnaik, Surya N.; Hopkins, Dale A. (Amsterdam ; Boston : Elsevier/Butterworth-Heinemann, 2004)
Strength of Materials provides a comprehensive overview of the latest theory of strength of materials. The unified theory presented in this book is developed around three concepts: Hooke's Law, Equilibrium Equations, and Compatibility conditions. The first two of these methods have been fully understood, but clearly are indirect methods with limitations. Through research, the authors have come to understand compatibility conditions, which, until now, had remained in an immature state of development. This method, the Integrated Force Method (IFM) couples equilibrium and compatibility conditions to determine forces directly. The combination of these methods allows engineering students from a variety of disciplines to comprehend and compare the attributes of each. The concept that IFM strength of materials theory is problem independent, and can be easily generalized for solving difficult problems in linear, nonlinear, and dynamic regimes is focused upon. Discussion of the theory is limited to simple linear analysis problems suitable for an undergraduate course in strength of materials. To support the teaching application of the book there are problems and an instructor's manual. Provides a novel approach integrating two popular indirect solution methods with newly researched, more direct conditions Completes the previously partial theory of strength of materials A new frontier in solid mechanics.
Determinate truss -- Simple beam -- Determinate shaft -- Simple frames -- Indeterminate truss -- Indeterminate beam -- Indeterminate shaft -- Indeterminate frame -- Two-dimensional structures -- Column buckling -- Energy theorems -- Finite element method -- Special topics.
"A new unified theory for the 21st century"--Cover.
Includes index.
Includes bibliographical references and index.
Keywords: Strength of materials; Electronic books